A Foreign Body in the Rectum - Islam, Md. Tanuvirul; Baqui, Brig Gen Mohammad Abdul; Ahmed, Siddique; Begum, Nasrin (Journal of Bangladesh College of Physicians and Surgeons, 2013)
J Bangladesh Coll Phys Surg 2012; 30: 234-235 DOI: http://dx.doi.org/10.3329/jbcps.v30i4.14769